Food crop production by smallholder farmers in Southern Africa : challenges and opportunities for improvement - Muimba-Kankolongo, Ambayeba (Academic Press, 2018)
Food Crop Production by Smallholder Farmers in Southern Africa: Challenges and Opportunities for Improvement evaluates traditional cultivation practices used by smallholder farmers, providing a synthesis of the latest information on increasing crop yield through adoption of research innovations. The book catalogs smallholder cultivation practices and recommends innovative strategies for improving the agriculture sector including: management practices that reduce net carbon emissions; technologies that improve soil structures and conserve the natural resources base; means of empowering female resources along value chains; and government commitment to adopt policies that enhance agriculture productivity by encouraging farmers to use environmentally sound cultivation technologies. Traditional farming techniques often produce negative impacts on the environment and ecosystem resulting in outbreaks of diseases and pests. In addition to the region's recurrent droughts, these outbreaks of numerous diseases and pests, weeds and other invasive plants put thousands at risk of poverty and hunger, as well as malnutrition. This book presents enhanced agricultural production technologies for ensuring adequate food production, safety and nutritional quality for the population of Southern Africa and forms the basis for an increased SADC regional effort in food production through which financial and trade institutions can improve stakeholder capacities, encourage micro-enterprise development and enhance employment and regional trade.